The use of social media in scientific research and creative thinking. (September 2019) - Busquet, Francois; Vinken, Mathieu
Abstract: Young researchers dedicate rightfully most of their time to core knowledge production via laboratory experiments, reading peer-review literature, publishing own results, attending conferences whenever possible as well as undertaking trainings on writing grants, papers among many other activities However, the authors argue here that restricting them to this unique set of activities is jeopardizing creativity and reducing awareness of a more complex picture in science. Other fields linked with social sciences, including scientometrics and epistemological areas covered during conferences and continuous education, may contribute to a more productive working environment for young researchers. To illustrate this, a smart use of social media is described as well as an example of a session. Furthermore, some general suggestions for implementing these activities and opening silos are discussed to increase creative thinking and to make in fine better science. Highlights: Besides conventional skills' set for young researchers, there are not enough incentives to perform creative thinking Smart use of social media such as Twitter may provide new ways to interact with lay audience and new collaborators Creative thinking should be about making scientists more open to the global picture by: Learning to become an "honest broker" in science, reaching out public with social media or using visuals for storytelling Tackling fraud, probity, conflict of interests, or gender inequality Facilizing cross-fertilization of ideas by providing placeholders to nurture creativity and discussion within researchers